Heavy burdens : stories of motherhood and fatness - Verseghy, Judy, 1982-; Abel, Sam, 1990- (Demeter Press, 2018)
"Heavy Burdens: Stories of Motherhood and Fatness seeks to address the systemic ways in which the moral panic around obesity impacts fat mothers and fat children. Taking a life-course approach, the book begins with analyses of the ways in which fatphobia is enacted on pregnant (or even not-yet-pregnant) women, whose bodies immediately become viewed as objects warranting external control by not only medical professionals, but family members, and even passers-by. The story unfolds as adults recount childhood stories of growing up fat, or growing up in fear of being fat, and how their mothers relationships with their own bodies and attempted weight-loss experiences shaped how food, exercise, and body management were approached in their homes in sometimes harmful ways. Finally, the book concludes with stories of women who have since become mothers, examining the ways in which having their own children altered their views on their own bodies and their perceptions of their mothers actions, and working to find fat-friendly futures via their own parenting (or grand-parenting) techniques. This book contains the artwork, stories, and analyses of nearly 20 contributors, all of whom seek to change the ways in which fatness is perceived, experienced, and vilified. It is the editors hope that these works will compel readers to reconsider their negative views on fatness and to retain softness toward every mother and child who are simply fighting to exist in the face of fatphobia"--Back cover